Analisis Penerapan Interpretasi Standar Akuntansi Keuangan (ISAK) 35 Tentang Penyajian Laporan Keuangan Entitas Non-Profit Pada Masjid Besar Ciparay - Meilani Purwanti; Febby Yulian (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The development of technology has increased the demand for transparency and accountability of public sector organizations, including mosques, in the preparation of financial reports in accordance with ISAK 35. This study aims to analyze the process of preparing the financial statements of the Ciparay Grand Mosque and its compliance with ISAK 35. The research method used is qualitative with a case study, through semi-structured interviews and documentation. The results showed that the Ciparay Grand Mosque has used the Maslam application to prepare financial reports digitally, but the reports generated are still limited to recording cash receipts and disbursements. The financial statements presented are not in accordance with ISAK 35, which should include a statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements. The contribution of this research is to provide practical guidance for religious non-profit organizations, especially mosques, in implementing ISAK 35. Thus, this research is expected to increase the accountability and transparency of mosque financial management, and strengthen public trust in religious non-profit organizations